An evaluation of mass-balance methods applied to Castle creek Glacier, British Columbia, Canada. Issue 220 (2014) - Beedle, Matthew J.; Menounos, Brian; Wheate, Roger
Abstract: We estimate the glacier mass balance of a 9.5 km 2 mountain glacier using three approaches for balance years 2009, 2010 and 2011. The photogrammetric, GPS and glaciological methods yielded sampling densities of 100, 5 and 2 points km -2, with measurement precisions of ± 0.40, ± 0.10 and ± 0.10 m w.e. respectively. Our glaciological measurements likely include a positive bias, due to omission of internal and basal mass balance, and uncertainty in determining the interface between snow and firn with a probe (±0.10 m w.e.). Measurements from our photogrammetric method include a negative bias introduced by the manual operator and our temperature index model used to correct for different dates of imaging (0.15 m w.e.), whereas GPS measurements avoid these biases. The photogrammetric and GPS methods are suitable for estimating glacier-wide annual mass balance, and thus provide a valuable measure that complements the glaciological method. These approaches, however, cannot be used to estimate mass balance at a point or mass-balance profiles without a detailed understanding of the vertical component of ice velocity.